Perception Versus Actual Value of Quality of Drinking Water: A Case Study of Iron and Steel Industry in West Bengal, India - Rahul Rajak, Arup Jana, Aparajita Chattopadhyay, Sushmita Singh and Jitender Prasad (Nature Environment and Pollution Technology, 2023)
The study aims to understand employees’ knowledge, awareness, and overall perception of drinking water quality in the Iron and Steel Industry in Burnpur, India. Further, this study evaluated drinking water’s physicochemical and bacteriological properties collected from different company sites. This study uses a mixed-method approach with individual interviews of selected employees (n=342) and the laboratory test of eight selected drinking water sites. The results show that most employees considered drinking water acceptable to be excellent. However, only 30% of employees in Site 1 (Coke Oven By-Product department) have reported organoleptic properties of water under the excellent category. The result explained that other physicochemical and bacteriological properties are in good status in all sites except for a colony count, expressing their suitability for drinking purposes. In summary, employees’ perception of water quality aligns with their drinking water’s physicochemical and bacteriological properties.